Nano hydrogen production material as well as preparation method and application thereof

Hollow organic-inorganic nanohybrid materials were synthesized by microwave heating, and metal and sulfide nanoparticles were introduced to limit the domain growth of CdS, which solved the stability and purity of traditional nanohybrid materials, and achieved efficient photocatalytic hydrogen production and Dye degradation effect.

CN119425804AInactive Publication Date: 2025-02-14HUBEI UNIV OF TECH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411501686.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The synthesis method of traditional organic-inorganic nanohybrid materials has problems such as poor material stability, low purity and few effective components, which limits its application in the fields of catalysis, energy conversion and sensing.

Method used

The hollow organic-inorganic nanohybrid materials with specific three-dimensional morphology were synthesized by microwave heating method, and the M@H-BDC-Zr/CdS photocatalyst was prepared by introducing metal nanoparticles and sulfide nanoparticles to limit the domain growth of CdS, and the M@H-BDC-Zr/CdS photocatalyst was prepared. .

Benefits of technology

The high-efficiency photocatalytic decomposition of aquatic hydrogen and dye degradation reactions of nano-hydrogen-producing materials is achieved, and the visible light absorption and charge transfer capabilities of the photocatalyst are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425804A_ABST
    Figure CN119425804A_ABST
Patent Text Reader

Abstract

The invention provides a nano hydrogen production material as well as a preparation method and application thereof, and the method comprises the following steps: mixing metal nanoparticles, inorganic metal zirconium salt, binary aromatic carboxylic acid and an acetic acid aqueous solution, carrying out microwave-assisted heating reaction, cooling at room temperature, and centrifuging to obtain a product 1; uniformly mixing the product 1 with a monobasic fatty acid aqueous solution, carrying out microwave reaction, cooling at room temperature, purifying, centrifuging and drying to obtain a product 2; the product 2 and a transition metal salt ethanol solution are subjected to ultrasonic uniform mixing, then a thioacetamide aqueous solution is dropwise added, a microwave reaction is carried out, after the reaction is completed, room temperature cooling and purification centrifugal drying are carried out, and the nano hydrogen production material is obtained. According to the invention, a microwave method is adopted to simply, conveniently and rapidly prepare the nano cadmium sulfide with a wrinkled surface and an octahedral hollow structure, the nano cadmium sulfide with visible light absorption grows in a pore channel of the organic-inorganic hybrid nano hybrid material in a confinement manner, and the prepared photocatalyst shows excellent catalytic performance of photocatalytic decomposition of water to produce hydrogen.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of materials, and in particular to a nano hydrogen-generating material and a preparation method and application thereof. Background Art

[0002] Organic-inorganic hybrid materials are mixtures of organic hydrocarbons and inorganic metals that combine multiple functional groups at the atomic or molecular scale to form synergistic functions. Traditional hybrid materials, such as coatings and rubbers, are hybrid materials made by mixing large molecular organic polymers with various inorganic substances. Due to the disadvantages of large molecular organic polymers such as high viscosity, high mass transfer resistance, and difficulty in mixing evenly with small molecular inorganic substances, the application of traditional hybrid materials is greatly limited. The organic-inorganic nano-hybrid material to which the present invention relates is a new type of nano-scale material with a periodic crystal structure prepared by combining small molecular organic substances with inorganic metals through chemical reactions. This new preparation method enables organic-inorganic nano-hybrid materials to exhibit many novel properties. Under the close combination of small molecular organic substances and inorganic metals, they interact with each other and form nano-hybrid materials, which can achieve the regulation of properties such as electron transfer and light absorption, thereby making this material widely used in catalysis, energy conversion, and sensing.

[0003] Due to the diversity of small molecule organic matter, a variety of nano-hybrid materials can be obtained by using different organic matter in chemical reactions. This is because different organic matter has different coordination effects with inorganic metals, thereby changing the formation of nano-hybrid materials and obtaining nano-hybrid materials with different morphologies. The change in morphology will have a great impact on chemical reactions. The present invention converts the pre-prepared organic-inorganic nano-hybrid material into a hollow structure by treating it with a carboxylic acid small molecule organic matter. The formation of the hollow structure gives it a large specific surface area, shortens the material transmission distance, and the cavity increases the reflection path of sunlight inside the material, enhances light absorption, and improves the performance of photocatalytic hydrogen production applications.

[0004] Traditional methods for synthesizing organic-inorganic nanohybrid materials, such as the sol-gel method and the interfacial reaction method, have some disadvantages. For example, the synthesized nanohybrid materials require post-processing, have poor material stability, low purity, and few effective ingredients. These disadvantages increase the difficulty of the operation steps and the synthesis cost.

[0005] Therefore, in order to solve the above problems, it is necessary to develop a nano-hybrid material with a simple and easy preparation method and excellent hydrogen production performance. Summary of the Invention

[0006] The purpose of the present invention is to provide a nano hydrogen-producing material and its preparation method and application. The preparation method is simple and easy to implement. The synthesized material has a specific uniform three-dimensional hollow structure and exhibits relatively excellent hydrogen production performance.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] In a first aspect of the present invention, a method for preparing a nanometer hydrogen-generating material is provided, the method comprising:

[0009] S1, mixing metal nanoparticles, inorganic metal zirconium salt or hafnium salt, dibasic aromatic carboxylic acid containing different functional groups, acetic acid and water, subjecting to microwave-assisted heating reaction, cooling at room temperature and centrifuging to obtain a solid product 1;

[0010] S2, mixing the solid product 1 and a monobasic fatty acid aqueous solution uniformly and performing microwave reaction, cooling at room temperature, and purifying by centrifugal drying to obtain a solid product 2;

[0011] S3, ultrasonically mixing the solid product 2 with a transition metal salt ethanol solution, then dropwise adding a thioacetamide aqueous solution and performing microwave reaction. After the reaction is completed, cooling at room temperature and centrifugation drying are performed to obtain a nano hydrogen production material.

[0012] Furthermore, in S1, the concentration of the aqueous solution of the metal nanoparticles is 1-10 mmol / L, the molar ratio of the inorganic metal zirconium salt to the dibasic aromatic carboxylic acid is 1:1, the amounts of the inorganic metal zirconium salt and the dibasic aromatic carboxylic acid are 0.64-2 mmol, the amount of acetic acid is 8-24 mL, and water is added so that the volume ratio of water to acetic acid in the system is 3-4:2.

[0013] Furthermore, in S1, the microwave power of the microwave-assisted heating reaction is 580-620W, and the reaction time is 20-60 minutes.

[0014] Furthermore, in S2, the mass volume ratio of the solid product 1 to the monobasic fatty acid aqueous solution is 80-120 mg:8.8-14 mL.

[0015] Furthermore, in S2, the microwave power is 580-620W, and the reaction time is 20-60 minutes.

[0016] Furthermore, in S3, the mass volume ratio of the solid product 2 to the ethanol solution of the transition metal salt is 40-200 mg:10-50 mL, the concentration of the ethanol solution of the transition metal salt is 0.031-0.184 mmol / L, and the concentration of the thioacetamide aqueous solution is 0.031-0.184 mmol / L.

[0017] Furthermore, in S3, the microwave power is 580-620W, and the reaction time is 1-5 minutes.

[0018] In a second aspect of the present invention, a nano hydrogen-generating material prepared by the method is provided.

[0019] In the third aspect of the present invention, the use of the nano hydrogen-generating material in the preparation of a photocatalyst is provided.

[0020] In a fourth aspect of the present invention, there is provided the use of the nano hydrogen-generating material in the preparation of degradable dyes.

[0021] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:

[0022] The present invention provides a method for preparing a nano-hydrogen-producing material, using a hollow organic-inorganic nano-hybrid material as a carrier. The hollow organic-inorganic nano-hybrid material is synthesized by microwave heating, has a specific three-dimensional morphology, and is simple and rapid to synthesize. A solution acid treatment is then performed to obtain a three-dimensional hollow structure. Metal nanoparticles and sulfide nanoparticles are introduced into the hollow organic-inorganic nano-hybrid material to obtain a three-dimensional hollow morphology with excellent hydrogen production performance. CdS is then confined to form the M@H-BDC-Zr / CdS photocatalyst, where M is a metal nanoparticle.

[0023] 2. The nano hydrogen-producing material photocatalyst prepared by the present invention has been proven to be an effective photocatalyst with a simple and easy preparation process. The prepared three-dimensional organic-inorganic nano hybrid material has a hollow structure and a micro / mesoporous hierarchical pore structure. It can integrate traditional organic and inorganic materials to give them semiconductor-like properties, ultimately giving them good photoelectric properties, effectively improving the photocatalyst's ability to absorb visible light and separate photogenerated electrons and holes. Therefore, it is a very promising photocatalyst.

[0024] 3. This invention successfully prepared a three-dimensional hollow organic-inorganic hybrid nanomaterial. The structure was demonstrated as an effective photocatalyst through photocatalytic water decomposition to produce hydrogen and dye degradation reactions. M@H-BDC-Zr / CdS exhibited high photocatalytic activity for the degradation of methylene blue and a high hydrogen production rate. This is due to the following reasons: 1) The M metal nanoparticles accelerated the transfer and separation of photogenerated electrons and holes, improving their lifetime and utilization; 2) The introduction of CdS expanded the light absorption range of the organic-inorganic hybrid nanomaterial; and 3) The hollow and micro / mesoporous hierarchical pore structure of the organic-inorganic hybrid nanomaterial increased the exposure of active sites and shortened the charge transfer distance. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0026] Figure 1 This is the XRD characterization pattern of Pt@H-BDC-Zr / CdS prepared in step (3) of Example 1;

[0027] Figure 2 This is a SEM image of Pt@H-BDC-Zr / CdS prepared in step (3) of Example 1;

[0028] Figure 3 is the nitrogen adsorption-desorption curve of Pt@H-BDC-Zr / CdS prepared in step (3) of Example 1;

[0029] Figure 4 This is the pore size distribution diagram of Pt@H-BDC-Zr / CdS prepared in step (3) of Example 1;

[0030] Figure 5 This is the catalytic performance diagram of the photocatalytic decomposition of water to produce hydrogen by Pt@H-BDC-Zr / CdS in Application Example 1;

[0031] Figure 6 This is the catalytic performance curve of the photocatalytic degradation of dyes by Pt@H-BDC-Zr / CdS in Application Example 1. DETAILED DESCRIPTION

[0032] The present invention will be described in detail below in conjunction with specific embodiments and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific embodiments and examples are for illustrating the present invention, rather than for limiting the present invention.

[0033] Throughout this specification, unless otherwise specified, the terms used herein should be understood as having the same meaning as commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. In the event of any conflict, the present specification shall take precedence.

[0034] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or obtained through existing methods.

[0035] The overall concept of the present invention is as follows:

[0036] Using the microwave heating method, organic-inorganic nano-hybrid materials with specific three-dimensional morphology can be prepared through microwave heating reaction in a water-acid mixed solvent system. Carboxylic acid is then used to treat the materials to obtain a three-dimensional hollow structure. Finally, CdS with visible light absorption is confined and grown within the pores of the organic-inorganic hybrid nano-hybrid materials. This synthesis method has the advantages of simple and rapid operation.

[0037] It should be noted that the present invention combines metal nanoparticles with organic-inorganic hybrid nanomaterials and introduces sulfide nanoparticles through an oil bath reaction to prepare a three-dimensional hollow hierarchical pore organic-inorganic hybrid nanomaterial, and uses it as a photocatalyst in a photocatalytic reaction.

[0038] The nano-hydrogen-producing material, which is prepared simply and quickly by microwave heating, has a wrinkled surface and an octahedral hollow structure. CdS with visible light absorption is confined and grown within the pores of the organic-inorganic hybrid nano-hybrid material. The prepared photocatalyst exhibits excellent catalytic performance in photocatalytic decomposition of water to produce hydrogen.

[0039] According to a typical embodiment of the present invention, a method for preparing a nanometer hydrogen-generating material is provided, the method comprising:

[0040] Step S1: mixing metal nanoparticles, an inorganic metal zirconium salt, a dibasic aromatic carboxylic acid and an acetic acid aqueous solution, subjecting the mixture to microwave-assisted heating reaction, cooling at room temperature and centrifuging to obtain a solid product 1;

[0041] In the S1,

[0042] The concentration of the aqueous solution of the metal nanoparticles is 1-10 mmol / L, the molar ratio of the inorganic metal zirconium salt to the dibasic aromatic carboxylic acid is 1:1, the amounts of the inorganic metal zirconium salt and the dibasic aromatic carboxylic acid are 0.64-2 mmol, the amount of acetic acid is 8-24 mL, and water is added to make the volume ratio of water to acetic acid in the system 3:2.

[0043] As a specific embodiment, the metal nanoparticles are selected from at least one of Pt, Pd, Cu, and Ru. The inorganic metal salt is selected from at least one of zirconium chloride, zirconium nitrate, zirconium sulfate, and hafnium chloride.

[0044] The microwave power of the microwave-assisted heating reaction is 580-620W, and the reaction time is 20-60 minutes.

[0045] Step S2, uniformly mixing the solid product 1 with a monobasic fatty acid aqueous solution and subjecting it to microwave reaction, cooling it to room temperature, and purifying it by centrifugal drying to obtain a solid product 2;

[0046] In the S2,

[0047] The dosage of the solid product 1 is 80-120 mg, and the volume of the monobasic fatty acid aqueous solution is 8.8-14 mL.

[0048] The oven heating reaction temperature is 90-110° C., and the reaction time is 10-14 hours.

[0049] Step S3, ultrasonically mixing the solid product 2 with a transition metal salt ethanol solution, then adding a thioacetamide aqueous solution dropwise and performing microwave reaction. After the reaction is completed, the mixture is cooled at room temperature and purified by centrifugal drying to obtain a nano hydrogen-generating material.

[0050] In the S3,

[0051] The amount of solid product 2 used is 40-200 mg, the amount of the transition metal salt ethanol solution used is 10-50 mL, the volume of the thioacetamide aqueous solution is 10-50 mL, the concentration of the transition metal salt in the transition metal salt ethanol solution is 0.031-0.184 mmol / L, and the concentration of the thioacetamide aqueous solution is 0.031-0.184 mmol / L. The microwave power is 580-620 W, and the reaction time is 1-5 minutes.

[0052] The inorganic metal salt in the embodiment of the present invention includes one of zirconium chloride and hafnium chloride.

[0053] The dibasic aromatic carboxylic acid containing a functional group includes one of 2-bromoterephthalic acid, 2-aminoterephthalic acid, 2-hydroxyterephthalic acid, and sodium sulfonate terephthalate.

[0054] Monobasic fatty acids include one of formic acid, acetic acid, propionic acid, butyric acid and lauric acid.

[0055] The transition metal salt in the transition metal salt ethanol solution includes one of cadmium acetate dihydrate, zinc acetate or cobalt acetate.

[0056] The present application will be described in detail below with reference to examples and experimental data.

[0057] Example 1

[0058] Preparation of the nanohydrogen-generating material Pt@H-BDC-Zr / CdS: 232 mg of zirconium chloride, 181 mg of 2-aminoterephthalic acid, 8 mL of an aqueous solution of Pt metal nanoparticles, 10 mL of deionized water, and 12 mL of acetic acid (ratio: 1 mmol: 1 mmol: 8 mL: 10 mL: 12 mL) were added to a microwave reactor, ultrasonically dispersed, and microwave-heated at 600 W for 1 hour. The resulting material was washed three times with water and then methanol, then dried at 80°C for 12 hours to obtain product 1. 100 mg of product 1 was added to 11 mL of a 5.76 mol / L aqueous solution of propionic acid, placed in a microwave reactor, ultrasonically dispersed, and microwave-heated at 600 W for 30 minutes. The hydrothermal reaction product was washed three times with water and then methanol, then dried at 60°C for 12 hours to obtain product 2.

[0059] 80 mg of product 2, 16.2 mg of cadmium acetate dihydrate, and 20 mL of ethanol were added to a microwave reactor and ultrasonically stirred until homogenized. A 40 mL aqueous solution containing 4.6 mg of thioacetamide was added dropwise. The mixture was then microwaved at 600 W for 1 minute. The resulting solid was washed three times with water and then ethanol, followed by drying at 80°C for 12 hours to yield Pt@H-BDC-Zr / CdS.

[0060] The Pt@H-BDC-Zr / CdS prepared in Example 1 was subjected to XRD test, and the test results are as follows: Figure 1 shown.

[0061] Depend on Figure 1 The XRD curve shows characteristic peaks for CdS, confirming its successful incorporation. Furthermore, characteristic peaks for H-BDC-Zr are observed between 5 and 10°, indicating a well-defined crystalline structure. However, the characteristic peaks for Pt metal nanoparticles are absent due to the low Pt loading and uniform dispersion.

[0062] Depend on Figure 2 The cracked shells shown in the SEM images indicate that the Pt@H-BDC-Zr / CdS has a hollow structure. Furthermore, the Pt@H-BDC-Zr / CdS has a three-dimensional morphology and a particle size of approximately 400 nm. The SEM images confirm the successful synthesis of the three-dimensional hollow nanostructures.

[0063] Depend on Figure 3 It can be seen that the nitrogen adsorption and desorption curve is a type IV adsorption isotherm, indicating that Pt@H-BDC-Zr / CdS has a micro / mesoporous hierarchical pore structure.

[0064] Depend on Figure 4It can be seen that the pore size distribution of Pt@H-BDC-Zr / CdS has both micropores and mesopores, which is consistent with Figure 3 The structures of the samples confirmed each other, proving the successful construction of the micro / mesoporous hierarchical pore structure.

[0065] Example 2

[0066] Preparation of the Nano-Hydrogen-Emitting Material Pt@H-BDC-Hf / CdS: This example was similar to Example 1, except that the zirconium chloride in Example 1 was replaced with an equimolar amount of hafnium chloride. The hydrogen-producing material Pt@H-BDC-Hf / CdS was successfully prepared and used in photocatalytic hydrogen production and methylene blue degradation experiments, with similar results to those in Example 1.

[0067] Example 3

[0068] Preparation of the Nano-Hydrogen-Emitting Material Pt@H-BDC-Br-Zr / CdS: This example was similar to Example 1, except that the 2-aminoterephthalic acid in Example 1 was replaced with an equal molar amount of 2-bromoterephthalic acid. The hydrogen-generating material Pt@H-BDC-Br-Zr / CdS was successfully prepared and used in photocatalytic hydrogen production and methylene blue degradation experiments, with similar results to those in Example 1.

[0069] Example 4

[0070] Preparation of the Nano-Hydrogen-Emitting Material Pt@H(BA)-BDC-Zr / CdS: This example is similar to Example 1, except that the aqueous propionic acid solution in Example 1 was replaced with an aqueous butyric acid solution of equal concentration. The hydrogen-producing material Pt@H(BA)-BDC-Zr / CdS was successfully prepared and used in photocatalytic hydrogen production and methylene blue degradation experiments, with similar results to those in Example 1.

[0071] Example 5

[0072] In this embodiment, the "cadmium acetate dihydrate" in Example 1 is replaced by "cobalt acetate", and the experimental results are similar to those in Example 1.

[0073] Example 6

[0074] In this embodiment, the "cadmium acetate dihydrate" in Example 1 is replaced by "zinc acetate", and the experimental results are similar to those in Example 1.

[0075] Comparative Example 1

[0076] Preparation of Nano-Hydrogen-producing Material Pt@BDC-Zr / CdS: This comparative example is similar to Example 1, except that the propionic acid aqueous solution is not used, thereby obtaining a solid structure Pt@BDC-Zr / CdS. Finally, the hydrogen-producing material Pt@BDC-Zr / CdS was successfully prepared and used in photocatalytic hydrogen production and methylene blue degradation experiments. The performance is shown in the attached figure. Figure 5 and 6 .

[0077] Application Example 1: Photocatalytic decomposition of water to produce hydrogen and degradation of dyes

[0078] In order to investigate the catalytic effects of the synthesized hollow morphology Pt@H-BDC-Zr / CdS and solid morphology Pt@BDC-Zr / CdS photocatalysts on the decomposition of water to produce hydrogen and the degradation of dyes, 20 mg of the Pt@H-BDC-Zr / CdS prepared in Example 1 and the Pt@BDC-Zr / CdS photocatalyst prepared in Comparative Example 1, in which the Pt loading amount was 0.8 wt% and the CdS loading amount was 9.2 wt%, were taken to test their catalytic effects on the photocatalytic reactions.

[0079] The test results are as follows Figure 5 and Figure 6 Shown are the catalytic performance diagram of photocatalytic decomposition of water to produce hydrogen and the catalytic performance curve of photocatalytic degradation of dyes.

[0080] Depend on Figure 5 It can be seen that the hydrogen production of Pt@H-BDC-Zr / CdS can reach 5281 μmol g after 3 h of light irradiation. -1 h -1 , showing a high level of hydrogen evolution; the hydrogen production of Pt@BDC-Zr / CdS can reach 1921 μmol g after 3 h of illumination. -1 h -1 The hydrogen production of the hollow structure Pt@H-BDC-Zr / CdS was significantly improved compared with that of the solid structure Pt@BDC-Zr / CdS, highlighting the advantages of the hollow structure in photocatalytic hydrogen production.

[0081] Depend on Figure 6 As shown, after 2 hours of light irradiation, the degradation rate of methylene blue (MB) reached 71.9% for Pt@H-BDC-Zr / CdS, demonstrating its excellent MB degradation performance. However, the degradation rate of MB for Pt@BDC-Zr / CdS after 2 hours of light irradiation was only 57.6%. The MB degradation rate of the hollow Pt@H-BDC-Zr / CdS was significantly higher than that of the solid Pt@BDC-Zr / CdS, demonstrating the advantages of the hollow structure in MB degradation.

[0082] Finally, it should be noted that the terms "comprises," "includes," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a list of elements includes not only those elements, but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.

[0083] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0084] Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if such changes and modifications fall within the scope of the claims and their equivalents, the present invention is intended to include such changes and modifications.

Claims

1. A method for preparing a nano hydrogen-generating material, characterized in that: The method comprises: S1, mixing a metal nanoparticle aqueous solution, an inorganic metal zirconium salt or hafnium salt, a functional group-containing dibasic aromatic carboxylic acid with acetic acid and water, performing a microwave-assisted heating reaction, cooling at room temperature and centrifuging to obtain a solid product 1; S2, mixing the solid product 1 and the monobasic fatty acid aqueous solution uniformly and performing microwave reaction, cooling at room temperature, purifying and centrifugally drying to obtain a solid product 2; S3, ultrasonically mixing the solid product 2 and the transition metal salt ethanol solution, then dropwise adding the thioacetamide aqueous solution and performing microwave reaction, after the reaction is completed, cooling at room temperature, purifying and centrifugally drying to obtain a nano hydrogen production material.

2. The preparation method according to claim 1, characterized in that: In S1, the concentration of the aqueous solution of the metal nanoparticles is 1-10 mmol / L, the molar ratio of the inorganic metal zirconium salt to the dibasic aromatic carboxylic acid containing a functional group is 1:1, the amounts of the inorganic metal zirconium salt and the dibasic aromatic carboxylic acid containing a functional group are 0.64-2 mmol, the amount of acetic acid is 8-24 mL, and water is added so that the volume ratio of water to acetic acid in the system is 3-4:

2.

3. The preparation method according to claim 1, characterized in that: In S1, the microwave power of the microwave-assisted heating reaction is 580-620W, and the reaction time is 20-60 minutes.

4. The preparation method according to claim 1, characterized in that: In S2, the mass volume ratio of the solid product 1 to the monobasic fatty acid aqueous solution is 80-120 mg:8.8-14 mL.

5. The preparation method according to claim 1, characterized in that: In S2, the microwave power of the microwave reaction is 580-620w, and the reaction time is 20-60 minutes.

6. The preparation method according to claim 1, characterized in that: In S3, the mass volume ratio of the solid product 2 to the ethanol solution of the transition metal salt is 40-200 mg:10-50 mL, the concentration of the ethanol solution of the transition metal salt is 0.031-0.184 mmol / L, and the concentration of the thioacetamide aqueous solution is 0.031-0.184 mmol / L.

7. The preparation method according to claim 1, characterized in that: In S3, the microwave power of the microwave reaction is 580-620W, and the reaction time is 1-5 minutes.

8. A nano hydrogen-generating material prepared by the method according to any one of claims 1 to 7.

9. Use of the nano hydrogen-generating material according to claim 8 in the preparation of a photocatalyst.

10. Use of the nano hydrogen-generating material according to claim 8 in the preparation of degradable dyes.

Citation Information

Patent Citations

  • Preparation method of silicone resin type organic / inorganic hybrid material for packaging

    CN102391529A

  • Inorganic nanoparticle in-situ modified polybenzimidazole proton exchange membrane and preparation method thereof

    CN103700874A

  • In-situ co-assembly synthesis adsorption-photocatalytic composite material based on UIO-66 and copper nanowires

    CN107159126A

  • TiO2 (at) MOF heterojunction photocatalyst with hollow frame morphology and preparation method thereof

    CN111514936A

  • Acid etching three-dimensional fold type hollow MOF catalyst as well as preparation method and application thereof

    CN112191274A